Application of twisted nematic cell in beam steering devices - Derfel, Grzegorz; Buczkowska, Mariola (Photonics Letters of Poland, 2015)
<!– saved from url=(0022)http://internet.e-mail –> Several simple beam steering devices composed of twisted nematic cells and typical optical elements are proposed. Principles of operation, based on elementary optical phenomena as total internal reflection or polarisation by reflection, are described. The deflection angles are calculated for exemplary parameters. The possibility of modifications of the proposed devices is discussed. Full Text: PDF References P. F. McManamon, P.J. Bos, M.J. Escuti, J. Heikenfeld, S. Serati, H. Xie, E.A. Watson, "A Review of Phased Array Steering for Narrow-Band Electrooptical Systems", Proc. IEEE 97, 1078 (2009). CrossRef S.-T. Wu, D.-K. Yang, Fundamentals of Liquid Crystal Devices (John Wiley & Sons, Chichester, 2006). X. Wang, D. Wilson, R. Muller, P. Maker, D. Psaltis, "Liquid-crystal blazed-grating beam deflector", Appl. Opt. 39, 6545 (2000). CrossRef T. Chan, E. Myslivets, J.E. Ford, "2-Dimensional beamsteering using dispersive deflectors and wavelength tuning", Opt. Expr. 16, 14617 (2008). CrossRef J. Kim, C. Oh, M.J. Escuti, L. Hosting, S. Serati, "Wide-angle nonmechanical beam steering using thin liquid crystal polarization gratings", Proc. SPIE 7093, 709302 (2008). CrossRef S. Valyukh, V. Chigrinow, H.S. Kwok, H. Arwin, "On liquid crystal diffractive optical elements utilizing inhomogeneous alignment", Opt. Expr. 20, 15209 (2012). CrossRef S. Valyukh, I. Valyukh, V. Chigrinov, "Liquid-Crystal Based Light Steering Optical Elements", Phot. Lett. Poland 3, 88 (2011). CrossRef A.B. Golovin, S.V. Shiyanovskii, O.D. Lavrentovich, "Gradient beam steering device based on a nematic cell with continuous ramp of the phase retardation", Proc. SPIE 5741, 146 (2005). CrossRef M. Bass et al., Handbook of Optics, vol. II 2nd Ed., Ch. 8, (McGraw Hill, New York, 1995). Schott (Optical Glass Data Sheets, 2012). DirectLink R. Herke, M.H. Anderson, T. Baur, Liquid crystal in precision optical devices (Meadowlark Optics, Inc., 2005).